Gênero e sexualidade na primeira infância: representações sociais de professoras da educação infantil - Sousa, Ana Lúcia de (2019)
This work was developed in the framework of the Postgraduate Program in Education, of the Center of Education of the Federal University of Paraíba, linked to the research line of Educational Policies and the Nucleus of Research and Studies on the Child. Having a qualitative nature, the research sought to analyse the social representations of teachers regarding Gender and Sexuality in Child Education. The research was held between 2018 and 2019, with 23 teachers as subjects, acting in four Centres of Reference in Children's Education (CREI) located in peripheral neighbourhoods of João Pessoa/PB. The thesis is based on the assumption that the school constitutes a space that legitimises the silence and/or denial of gender and sexuality issues, persisting in the surveillance and control of these phenomena in Child Education. As tools for obtaining the data, three questionnaires were applied (Profile Questionnaire, Word Evocation Questionnaire and Teaching Performance Questionnaire), in addition to the use of the Field Journal. The analysis and interpretation of the information collected were carried considering as basis the Content Analysis through Categorical Semantic Analysis and Interpretative Analysis. The results show that the social representations of teaching concerning Gender and Sexuality in the field of Child Education are still influenced by stereotypes that support teaching conceptions and that the School as an institution still supports both the denial of sexuality and negatively influence gender relations among children in Child Education. It is understood that this is a subject historically marked by taboos and prejudices that can culminate in actions and attitudes that can imprison children and childhoods. The need to change these paradigms is urgent, starting with the creation and maintenance of discursive and reflective spaces, with the aim of contributing so that teachers can face the challenges present in the daily life of Centres of Reference in Child Education (CREI) and outweigh the archaic conceptions that still underpin their pedagogical practices. We understand that teachers are in constant formation and to provoke in these professionals a process of continuous reflection on the relevance of the debate on the insertion of gender and sexuality categories in the field of children's education can mean a commitment in making the society less discriminatory and violent and more just and plural.